Dioscin ameliorates intestinal ischemia/reperfusion injury via adjusting miR-351-5p/MAPK13-mediated inflammation and apoptosis. (January 2019) - Zheng, Lingli; Han, Xu; Hu, Yupeng; Zhao, Xuerong; Yin, Lianhong; Xu, Lina; Qi, Yan; Xu, Youwei; Han, Xu; Liu, Kexin; Peng, Jinyong
Graphical abstract: Abstract: Inflammatory reaction and cell apoptosis are two important processes in intestinal ischemia/reperfusion (II/R) injury, and exploration of effective lead compounds against II/R injury via regulating inflammation and apoptosis is critical important. In this paper, the results indicated that dioscin significantly increased cell viability, and inhibited inflammation and apoptosis caused by hypoxia-reoxygenation (H/R) injury in IEC-6 cells. in vivo II/R injury, dioscin markedly suppressed inflamma- tion and apoptosis, improved pathological changes, and depressed chiu' score in rats. Mechanistic studies indicated that dioscin notably up-regulated the expression level of MAPK13 through decreasing miR-351-5p level, and thereby decreased the expression levels of p-PKD1, NF-κB, Apaf-1, cleaved Caspase-3 and cleaved Caspase-9. Furthermore, miR-351-5p mimic and inhibitor experiments in IEC-6 cells further proved that dioscin up-regulated MAPK13 expression by decreasing miR-351-5p level to inhibit inflammation and apoptosis. Therefore, dioscin showed protective effect against II/R injury via adjusting miR-351-5/MAPK13-mediated inflammation and apoptosis. Dioscin should be considered as one potent candidate and miR-351-5/ MAPK13 should be one effective drug target for the treatment of II/R injury.